The Poststroke Peripheral Immune Response Is Differentially Regulated by Leukemia Inhibitory Factor in Aged Male and Female Rodents. (10th December 2020) - Davis, Stephanie M.; Collier, Lisa A.; Messmer, Sarah J.; Pennypacker, Keith R.
Abstract : Background . The goal of this study was to determine whether leukemia inhibitory factor (LIF) promotes anti-inflammatory activity after stroke in a sex-dependent manner. Methods . Aged (18-month-old) Sprague-Dawley rats of both sexes underwent sham surgery or permanent middle cerebral artery occlusion (MCAO). Animals received three doses of intravenous LIF (125 μ g/kg) or PBS at 6, 24, and 48 h before euthanization at 72 h. Spleen weights were measured immediately following euthanization. Western blot was used to measure protein levels of CCL8, CD11b, CXCL9, CXCL10, IL-12 p40, IL-3, and the LIF receptor (LIFR) in spleen tissue. ELISA was used to measure IL-1 β, IL-6, TNF α, and IFN γ in spleen tissue. A Griess Assay was used to indirectly quantify NO levels via measurement of nitrite. Levels of cellular markers and inflammatory mediators were normalized to the baseline (sham) group from each sex. Statistical analysis was performed using two-way ANOVA and followed by Fisher's LSD post hoc test. Results . Aged female rats showed a significantly lower spleen weight after MCAO, but showed a significant increase in spleen size after LIF treatment. This effect was observed in aged male rats, but not to as great of an extent. CD11b levels were significantly higher in the spleens of MCAO+PBS males compared to their female counterparts, but there was no significant difference in CD11b levels between MCAO+LIF males and females. LIF significantly increased CXCL9 after LIF treatment in aged male and female rats. LIFR and IL-3 were upregulated after LIF treatment in aged females. Splenic nitrate increased after MCAO but decreased after LIF treatment in aged females. Splenic nitrate levels did not increase after MCAO but did increase after LIF treatment in aged males. The following cytokines/chemokines were not altered by sex or treatment: TNF α, IL-6, IL-12 p40, CCL8, IFN γ, and CXCL10. Conclusions . LIF treatment after permanent MCAO induces sex-dependent effects on the poststroke splenic response and the production of proinflammatory cytokines among aged rats.